RETRACTED: Exchange Rate Dynamics, Energy Consumption, and Sustainable Environment in Pakistan: New Evidence From Nonlinear ARDL Cointegration - Shah, Muhammad Haroon; Ullah, Irfan; Salem, Sultan; Ashfaq, Sara; Rehman, Alam; Zeeshan, Muhammad; Fareed, Zeeshan (Frontiers in Environmental Science, 2022)
Pakistan’s local currency has been devalued during different exchange regimes, which may substantially affect energy consumption and CO2 emissions. Therefore, this study investigates the effects of exchange rate depreciation on Pakistan's CO2 emissions and energy consumption from 1990-2018. We apply the nonlinear ARDL cointegration approach for the empirical analysis and found that exchange rate depreciation increases CO2 emissions and energy consumption both in the short and long run. These results suggest that currency devaluation has an expansionary effect which enhances economic growth at the cost of high energy consumption and CO2 emissions. Therefore, the government needs regulations along with an exchange rate policy to control CO2 emissions. Moreover, the government should search for alternate energy resources such as renewable energy resources that meet the country’s energy needs and mitigate CO2 emissions.